Peran Advokat dalam Pendampingan Kasus Pro Bono: Studi di Kantor Advokat Drs. Victor Asian Sinaga, S.H. - Ricky Leandro Putra Pramudika; Yudistira Kusuma Wardhana (CV. ITTC INDONESIA, 2026)
This research aims to analyze the role of advocates in assisting pro bono cases in the Office of Advocate Drs. Victor Asian Sinaga, S.H. The background of this research is based on the importance of access to justice for underprivileged communities who often face limitations in obtaining legal services. In the Indonesian legal system, the obligation of advocates to provide free legal aid has been regulated in Law Number 18 of 2003 concerning Advocates and strengthened through Law Number 16 of 2011 concerning Legal Aid. The research method used is qualitative research with a descriptive approach, through observation during internship activities and analysis of legal assistance practices carried out by advocates in handling pro bono cases. The results of the study show that advocates have an important role in providing legal assistance to underprivileged clients, which includes providing legal consultation, drafting legal documents, and assisting in the trial process. However, in its implementation, there are still several obstacles, such as limited time, resources, and low public understanding of the right to legal aid. Therefore, it is necessary to strengthen the role of advocates and support from various parties to increase the effectiveness of the implementation of pro bono legal aid in realizing access to justice for all people.